1953
DOI: 10.1071/ar9530526
|View full text |Cite
|
Sign up to set email alerts
|

Reactions and field resistance of some potato varieties and hybrids to the leaf-roll virus.

Abstract: The leaf-roll reactions of a number of potato hybrids and varieties have been defined by external symptoms and the extent of phloem necrosis present in stem sections. There is no constant correlation between the leaf-roll reaction and field resistance of varieties and hybrids. The variety Bismark had the highest leaf-roll resistance of any of the types tested so it should prove a useful parent for this character. The resistance of Bismark and some hybrids is apparently dependent upon a virus-inactivating mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Also, as mentioned above, we did not find resistance to phloem transport in stem sections of three other cultivars with A R. The study of fundamental features of virus transport was not an objective of this investigation. However, Hutton & Brock (1953) had previously suggested that cv. Bismark 'has a PLRV inactivating mechanism which is continually localising the virus and reducing its concentration so that even infected plants with severe symptoms produce varying percentages of progeny free of symptoms'.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, as mentioned above, we did not find resistance to phloem transport in stem sections of three other cultivars with A R. The study of fundamental features of virus transport was not an objective of this investigation. However, Hutton & Brock (1953) had previously suggested that cv. Bismark 'has a PLRV inactivating mechanism which is continually localising the virus and reducing its concentration so that even infected plants with severe symptoms produce varying percentages of progeny free of symptoms'.…”
Section: Discussionmentioning
confidence: 99%
“…Spunta leaves. As with feeding preference, the cultivar characteristic(s) responsible for different rates of colonization was independent of I R and A R. Hutton & Brock (1953) found that many progeny tubers from PLRV-infected plants of cv. Bismark were healthy.…”
Section: Aphid Feeding Preferences and Colonization Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many virus-free progeny tubers developed from plants with a primary (current season) infection of PLRV in potato cv. Bismark (Hutton & Brock, 1953) and clone G7445(1) (Barker, 1987 b). Wilson & Jones (1992) found that the rate of systemic movement of PLRV through grafted stem sections of cv.…”
Section: Introductionmentioning
confidence: 99%
“…Hypersensitive resistance is type of resistance that limits spread within the plant following the initial infection (Barker, 1987). This occurs when there is a lower percentage of a virus-infected daughter tuber from an infected plant resulting from impeded virus movement (Hutton and Brock, 1953). Tolerance is when there is little or no apparent effect on the infected plant especially when infected plants are symptomless or have reduced symptom expression in the presence of disease (Cooper and Jones, 1983).…”
Section: Types Of Potato Virus Resistancementioning
confidence: 99%